EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DAN THINK PAIR SHARE PADA MATERI OPERASI ALJABAR DITINJAU DARI KETERAMPILAN SOSIAL SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SEMARANG TAHUN PELAJARAN 2014/2015 - Noviana Sukma Dewi; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purposes of this study was to determine the effect of the learning models on the learning achievement in Mathematics viewed from the sosial skill of the students. The learning models compared were the cooperative learning model of the Think Talk Write (TTW) type with scientific approach, Think Pair Share (TPS) type with scientific approach, and classical model with scientific approach.The type of this study was a quasi-experimental study with a 3x3 factorial design. The study population were all of grade VII students of Junior High School in Kabupaten Semarang. Instruments used for data collection were mathematics achievement test and sosial skill questionnaire. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. Based on the hypothesis testing it can be concluded as follows. (1) Students’ learning achievement treated by TTW learning model with scientific approach are better than students treated by TPS model with scientific approach and classical learning model with scientific approach. In addition to, students’ learning achievement treated by TPS model with scientific approach are better than students treated by classical learning model with scientific approach. (2) Students’ learning achievement who have high social skill are better than students who have moderate and low social skill. Furthermore, students who have moderate social skill are better than students who have low social skill. (3) In high, moderate, and low social skill category, students learning achievement treated by TTW model with scientific approach are better than student who treated by TPS learning model with scientific approach and classical learning model with scientific approaching. Asides from that, students learning achievement are treated by TPS learning model with scientific approach are better than students who treated by classical learning model with scientific approach. (4) In TTW learning model with scientific approaching, TPS with scientific approach and classical learning with scientific approach, students learning achievement who have high social skill are better than students who have moderate and low social skill. Moreover, students who have moderate social skill are better than students who have low social skill.Keywords: Think Talk Write (TTW), Think Pair Share (TPS), Scientific Approach, Student Social Skill.